PENGARUH GAYA KEPEMIMPINAN, SEMANGAT KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. SYANDI PUTRA MAKMUR CABANG KOTA BENGKULU - Ige Sepriansya; Ratnawili Ratnawili; Meilaty Finthariasari ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
This study aims to determine: (1) the influence of leadership style on the performance of employees of PT. Syandi Putra Makmur Cabang Bengkulu City. Jl. Wr. Suparman Talang Kering, Pematang Village, Governor of Muara Bangkahulu Subdistrict, Bengkulu City (2) The influence of work motivation on the performance of the employees of PT. Syandi Putra Makmur Vabang Bengkulu City. Jl. Wr. Suparman Talang Dry, Pemarang Village, Governor of Muara Bangkahulu Sub-District, Bengkulu City (3) The effect of compensation on the performance of the employees of PT. Syandi Putra Makmur Cabang Bengkulu City. Jl. Wr. Suparman Talang Kering Pematang Village, Governor of Muara Subdistrict, Bangkah, the Capital of Bengkulu. This research method is quantitative with a population of 68 people which will use the sampling technique formula meaning the whole respondent. Data collection techniques using observation and questionnaires, the research variables are leadership style (X1) morale (X2) compensation (X3) and employee performance (y). the results of multiple linear equations y = 8,689 + 0.289 (X1) + 0.384 (X2) + 0.230 (X3). Hypothesis testing results leadership style variables (X1) morale (X2) and compensation (X3) f test results obtained fig 27,988 and the significance value (sig) 0,000 results can be interpreted as a significance value of 0,000<0.050 then it can be interpreted that H3 is accepted means simultaneously the leadership style, morale and compensation variables significantly influence employee performance at PT. Syandi Putra Makmur Bengkulu City Branch Jl. Wr. Suparman Talang Kering, Pematang Urban Village, the Governor of Muara District, Bangkahulu, Bengkulu City. The results of the t count of the leadership style variable (X1) were 2,244 and the significant value (sig) of 0.028 meant 0.028<0.050, the morale variable (X2) was 2.666 and the significant value (sig) of 0.010 meant 0.010<0.050. and compensation variable (X3) is 2,721 and significant value (sig) 0.008 means 0.008 <0.050 then Ha hypothesis is accepted in other words leadership style (X1) morale (X2) and compensation (X3) significantly influence employee performance at PT. Syandi Putra Makmur Bengkulu City Branch Jl. Wr. Suparman Talang Kering Pematang Village, Governor of Muara District, Bangkahulu, Bengkulu City. Keywords : Leadership Style, Work Spirit, Compensation and Employee Performance